Pengaruh Bahasa Gaul Terhadap Eksistensi Bahasa Indonesia - Jamila, Siti; Hasani, Nur; Salsabila, Qotrunnada Anis; Susetya, Hemas Haryas Harja (Universitas Asahan, 2025)
This study discusses the influence of slang on the existence of the Indonesian language amid the rapid development of digital technology and the widespread use of social media. The phenomenon of slang, which is commonly used by young generations on platforms such as TikTok, WhatsApp, and Instagram, reflects linguistic creativity while also posing challenges to the preservation of the Indonesian language. This research was conducted using a qualitative method through literature review, analyzing relevant sources related to the forms, functions, as well as the positive and negative impacts of slang usage on the ability to speak proper and correct Indonesian. The findings show that slang can enrich vocabulary and serve as a means of self-expression, yet excessive use may disrupt formal communication and accelerate language shift. Therefore, active roles from parents, educators, the government, and the media are necessary to instill a love for the Indonesian language and encourage its proper usage in order to maintain its existence in the era of globalization.